Dream scenario [videorecording (Blu-Ray + DVD)] - Borgli, Kristoffer, 1985-; Cage, Nicolas, 1965-; Nicholson, Julianne, 1971-; Cera, Michael; Meadows, Tim, 1961-; Gelula, Dylan, 1994-; Baker, Dylan; Clement, Jessica (Lionsgate, 2024)
Hapless family man Paul Matthews finds his life turned upside down when millions of strangers suddenly start seeing him in their dreams. When his nighttime appearances take a nightmarish turn, Paul is forced to navigate his newfound stardom.